Hubungan Usia dan Pendidikan Ibu Hamil dengan Pencegahan Stunting di Puskesmas Talang Banjar Kota Jambi - Apriana, Tiwi; Ningsih, Nisa Kartika; Afriayani, Lusi; Hariyanti, Reni (Universitas Batanghari Jambi, 2024)
The aim of this research is to determine the relationship between age and children's education. pregnant women and stunting prevention measures at the Talang Banjar Community Health Center in 2024. This research is a quantitative exploratory study with cross sectional research. The research sample consisted of 32 pregnant women who visited the Talang Banjar Community Health Center during their pregnancy and filled out a questionnaire. The analysis tool in this research uses the chi-square test. The results of this research reveal that there is a relationship between the age and education of pregnant women and stunting prevention measures at the Talang Banjar Community Health Center, Jambi City in 2024.